A high-performance electric motor drive for electric aircraft application - Zhang, Yuhui (Nanyang Technological University, 2024)
This dissertation provides a comprehensive investigation into different motor types, focusing on the applicability of the FSPM motor in electric aircraft. Through meticulous research, six enhanced FSPM (Flux-Switching Permanent Magnet) motor topologies were developed. The operating principles of these motors were analyzed, and further explanations were provided regarding their winding methods, materials, parameters, etc. Simulation results highlighted the superior torque performance of E-core machines. Despite employing only half the magnets compared to traditional designs, E-core 12-stator-pole 11-rotor-pole motor exhibit a higher average output torque at low currents. Furthermore, experimental testing revealed that dual three-phase configurations offer improved performance and resilience against single-phase faults when compared to conventional three-phase motors, providing valuable insights into their practical implementation.